EDUKASI, PENDAMPINGAN, DAN OPTIMALISASI PEMBERDAYAAN SUMBER DAYA MANUSIA KEWIRAUSAHAAN EKONOMI KREATIF KOMUNITAS GEN-Z - Zandra Dwanita Widodo; Sri Wijiastuti; RINI ADIYANI; Laksono Sumarto; atik lusia; Darsono; Syahri Alhusin; Dwinanda Ripta Ramadhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2024)
A community service program aimed at the Karangtaruna community, which is part of the young generation of Gen Z, will be implemented to assist and optimize the empowerment of human resources in Boyolali village. This program provides stimulus with the following targets and stages: 1) Preparation stage for creative economy business management practices and recording financial transactions, 2) Practicum stage where the process of running a business is carried out by the young generation of Gen Z with assistance and monitoring by the service team, as well as direction and evaluation, 3) Activity reporting stage where the young generation of Gen Z reports on developments in turnover, business transactions, production processes, marketing and financial reporting. The results of this activity include: increasing entrepreneurial performance in the Gen Z community who are more empowered and independent, increasing entrepreneurial knowledge which helps them in marketing products and services, and generating enthusiasm and positive energy among Gen Z to continue entrepreneurship. This activity went well and effectively.